Analisis SWOT Terhadap Penerapan Pembelajaran Tematik di MI Ma’arif NU 1 Pengadegan Kecamatan Pengadegan Kabupaten Purbalingga - Khamim, Khamim; Wiyani, Nova Ardy (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to provide a SWOT (Strength, Weakness, Opportunity, Threats) analysis to the implementation of thematic learning in MI Ma'arif NU 1 Pengadegan. The SWOT analysis carried out was seen from various aspects, namely aspects of the headmaster, teachers, students, curriculum, and infrastructure. The approach that is used in this research is a descriptive analytical approach, namely an approach that describes the facts that exist in the field. This study has resulted in the conclusion that in general the implementation of thematic learning in MI Ma'arif NU 1 Pengadegan is not perfect. The strengths and opportunities are proportional to the weaknesses and challenges it has. This fact gives the conclusion that minimizing and even annulling all weaknesses and challenges, while optimizing strengths and opportunities will make the thematic learning in MI Ma'arif NU 1 Pengadegan better.